Serapan Tenaga Kerja Pada Budidaya Ikan Patin dalam Kolam di Kabupaten Banjar, Kalimantan Selatan - Irma Febrianty (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2020)
The difference in pond area owned by catfish cultivators will result in differences in pond management so that the wider the pond, the more manpower needed and the worker specifications required by the cultivators. The purpose of this research is to see the labor absorption in catfish culture in ponds, as well as the labor value according to the specifications of the type of work required. The data analysis method uses descriptive analysis for the amount of labor absorbed and Oppurtunity cost, namely what benefits the workforce gets in working in catfish farming. Labor absorption in catfish farming in ponds for large scale businesses requires permanent labor to maintain the pond. as many as 4 people and harvest labor also requires as many as 8 - 9 people. Medium-scale businesses require 1-3 permanent workers and 5-7 panensian workers, while small scale businesses do not require permanent workers to maintain the pond because they are guarded by themselves and require 5-6 harvest workers. The value of the labor resources absorbed in catfish culture in the pond is Rp. 436,608,000.00. Keywords: Labor, Cultivation, Catfish.